New and Future Member States: Romania’s Role in the EU-27 - Mugur Isărescu (Romanian Journal of European Affairs, 2005)
The logic of history urges me to believe that the enlargement process,pondered over thoroughly, will no longer be stopped. Therefore, talking today about Romania’s role in a EU with 27 countries cannot be an action against history’s mainstream. On the contrary, I consider this action natural and necessary. In a multipolar world, characterized by an increasing competition among the big blocks of countries, Europe is condemned to a continuation of the deepening of integration, unless it wants to turn itself into a museum of civilization, good only for future entertainment of American, Japanese, Chinese and, why not, Indian tourists.